Effective pain therapy can improve the survival of patients with pancreatic cancer - Ozcan, Sibel; Akin, Sevim; Yildiz Altun, Aysun; Bolat, Esef; Ates Onal, Selami (Kare Publ, 2019)
Objectives: In this study, characteristics and analgesic treatment of patients with pancreatic cancer who applied to the algology clinic were evaluated. Methods: Demographic characteristics, pathologic diagnosis, metastasis, cancer treatment, and analgesic interventions in 60 patients with pancreatic cancer, referred to the algology clinic, were examined. Results: The application time of the patients to the clinic was 3.9 +/- 0.92 months after the diagnosis, and the visual analog scale (VAS) was 6.96 +/- 0.11 at the initial assessment. According to the analgesic step ladder protocol, a nonopiod + weak opioid + strong opioid (transdermal) were applied in 58.33%, a nonopioid + weak opioid + strong opiod (oral) in 5%, and nonopiod + weak opioid in 36.66% of the patients. Adjuvant pain medications were used in 68.33% of the patients (benzodiazepine, 80.48%; antidepressant, 19.51%), while no adjuvant was used in 31.66% of the patients. While the mean survival time for patients with pancreatic cancer changed from 3 to 6 months, it was 8.48 +/- 7.46 months for patients who applied to the pain clinic. Conclusion: Abdominal pain in pancreatic cancer is the most common symptom that negatively affects the quality of life. A good analgesia improves the survival, while pain decreases the survival. The results of the present study demonstrated that the survival of the patients with metastatic pancreatic cancer who received effective pain therapy in the algology clinic may be longer.
Etkin ağrı tedavisi pankreas kanserli hastalarda sağkalımı artırabilir
Keywords: Survival; pancreatic cancer; pain; visual analog scale